Regulation of ERG3, ERG6, and ERG11 Genes in Antifungal-Resistant isolates of Candida parapsilosis - Lotfali, Ensieh (Iran Biomed J, 2017)
BACKGROUND: Candida parapsilosis is one of the five common strains of yeasts involved in invasive candidiasis. The expression analysis of sterol biosynthesis pathway genes, which are associated with resistance, can assist the better understanding of antifungal resistance mechanisms. METHODS: The antifungal susceptibility of 120 clinical C. parapsilosis isolates was examined. The changes in the gene expression related to resistance were analyzed. RESULTS: Eight strains were resistant to fluconazole (FLC), itraconazole (ITC), and amphotericin B (AMB). The regulation variations included increased mRNA levels of ERG3, ERG6, and ERG11 and decreased mRNA levels of ERG3 and ERG6 in response to FLC. ERG11 mRNA level increases in response to ITC and AMB. CONCLUSION: The mechanism of resistance to azoles in C. parapsilosis is very similar to C. Albicans. This feature may help to design new treatment strategy for candidiasis